Construction and demolition waste as a source of PVC for recycling - Darbello Prestes, Sabrina Moretto [UNESP]; Mancini, Sandro Donnini [UNESP]; Rodolfo, Antonio; Keiroglo, Raquel Carramillo [UNESP] (Sage Publications Ltd, 2012)
Construction and demolition waste can contain considerable amounts of polyvinyl chloride (PVC). This paper describes a study of the recycling of PVC pipes collected from such waste materials. In a sorting facility for the specific disposal of construction and demolition waste, PVC was found to represent one-third of the plastics separated by workers. Pipes were sorted carefully to preclude any possible contamination by poly(ethylene terephthalate) (PET) found in the waste. The material was ground into two distinct particle sizes (final mesh of 12.7 and 8 mm), washed, dried and recycled. The average formulation of the pipes was determined based on ash content tests and used in the fabrication of a similar compound made mainly of virgin PVC. Samples of recycled pipes and of compound based on virgin material were subjected to tensile and impact tests and provided very similar results. These results are a good indication of the application potential of the recycled material and of the fact that longer grinding to obtain finer particles is not necessarily beneficial.
Keywords: Recycling; polyvinyl chloride (PVC); construction and demolition waste; mechanical properties; pipes; plastics